Deception and Drug Acquisition - Amber N. Sanders; John M. Eassey; John M. Stogner; Bryan Lee Miller (SAGE Publishing, 2016)
Purpose: Most research examining patient-based drug diversion neglects to assess physician deception directly. We attempt to determine if motives for deception are linked to success, and, similarly, if any health, demographic, or substance use history characteristics of the patients are predictive of being able to successfully deceive a physician. Methods: Stratified random sampling was utilized to obtain a sample of 2349 young adults. Respondents completed a survey detailing their substance use histories and whether they had ever deceived a physician for medication. Ninety-three of these respondents reported attempting to deceive a physician for a medication and compose the analytic sample for the study. Results: Of the 93 young adults who reported having attempted to deceive a physician for pharmaceuticals (4.0% of the general sample), 64 (68.8%) were successful. This included 24 only seeking medications for their own use, 9 only for financial purposes, and 31 with both motives. Respondents who reported recreationally using pharmaceuticals in the past were more likely to report successful attempts at obtaining a prescription compared with respondents without a history of abuse. With respect to demographic characteristics of the respondents, only race/ethnicity distinguished between successful attempts and failure. Conclusions: Although a rare occurrence in the overall sample, significant correlates of successful deception did emerge. Respondents motivated to obtain a prescription in order to sell it to others were overwhelmingly likely to succeed in their pursuit to deceive as compared with respondents who sought prescriptions for their own abuse. Successful deceivers were also more likely to have been legitimately prescribed medication in the past. Successful respondents were more likely to be Caucasian than any other race/ethnicity.